1991
DOI: 10.1007/bf00128950
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial cell morphology under permanent wear of rigid contact lenses

Abstract: The influence of the permanent wear of rigid high Dk-lenses (nominal Dk 71 or 92) with elliptical geometry on the corneal endothelium was assessed. For this purpose the endothelium of 16 patients was compared by specular microscopy before and after the permanent wear. The wearing time of the lenses varied between 7 and 24 months. Computerized morphometric analysis of the photographs revealed that the variability in cell size (polymegathism) and in cell shape (pleomorphism) did not change during the wearing per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…14 A review of the literature, however, reveals that wearing RGP lenses does not induce significant changes in endothelial cell density. [15][16][17] Morphologic changes in endothelial cells were first noted in a group of PMMA lens wearers by Schoessler and Woloschak. 18 The changes included an increased variability in cell size (polymegethism) and an increased variability in cell shape (pleomorphism).…”
Section: Discussionmentioning
confidence: 95%
“…14 A review of the literature, however, reveals that wearing RGP lenses does not induce significant changes in endothelial cell density. [15][16][17] Morphologic changes in endothelial cells were first noted in a group of PMMA lens wearers by Schoessler and Woloschak. 18 The changes included an increased variability in cell size (polymegethism) and an increased variability in cell shape (pleomorphism).…”
Section: Discussionmentioning
confidence: 95%
“…Rigid gas-permeable (RGP) lenses, and silicone lenses have not been observed to induce changes in endothelial morphology (Schoessler et al 1984, Nieuwendaal et al 1991. Even endothelial cells of corneal transplants tolerate RGP lens wear well (Speaker et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in the introduction, from a perspective that the introduction of RGP lenses would result in much lower endothelial polymegethism compared to PMMA lens wear, the early evidence presented to support such an expectation does not appear to be substantial [16][17][18][19][20][21], although there was relatively little data available at that time on how fast (or slowly) polymegethism might develop. Notwithstanding, from this perspective it is perhaps surprising that the more recent report indicated that average COV values of close to 40 % could be present after longer term RGP lens wear and so some would have even higher COV values [22].…”
Section: Discussionmentioning
confidence: 99%